O serviço social e a questão socioambiental: uma discussão necessária e propositiva - Machado, Neide Maria Serpa (My University, 2021)
The present study is a undergraduate thesis for the Social Service Course whose central theme proposes to approach the environmental issue as an expression of the social issue from the comprehension of the totality of contemporary social reality, against the background of the hegemonic capitalist system. With the current ecological crisis, the world society has faced the biggest challenge in terms of the need to change actions in the face of this issue. In the face of such a crisis, considered socio-environmental, the Social Work, as a profession that is part of the fabric of social relations, should not remain indifferent to this theme. So, the research problem consists in understanding how the professional Social Worker has been contributing to the socio-environmental problem in contemporary society. We seek in the trajectory of this research to deepen the problematization of the manifestations of the socio-environmental issue in a socio-historical perspective, to reflect on the possible interventional contributions of the social worker. Based on Marx's dialectical materialist perspective, highlighting the categories historicity, contradiction, mediation, totality and work, we tried to reflect about the developments and new outlines of the socio-environmental issue, packed by capitalism whose premise is the accumulation of wealth through force human labor that supplies and generates income to the owners of the means of production. To carry out bibliographic and documentary research, various sources were used, such as legislation, articles, books, documents from national and international conferences, among others. The research starts from the analysis of the existing relationship between man, nature and work from the times when he sought in nature his means for subsistence, up to the current capitalist production and reproduction and the responses of the Brazilian State to these problems. We also sought to understand how the Social Worker has been inserted in socio-environmental issues and what are the challenges for the work of this professional in relation to these issues, seeking to discuss the importance and the need to know and expand the debate on the subject in the area of Social Work. In conclusion, it is clear that the ecosystem has suffered the consequences of capitalism and has been destroyed on a daily basis. Under the aegis of capital, humanity has been deepening its path of destruction of nature, at increasingly disturbing levels. The evidence for this process is found in the scarcity of non-renewable resources in the levels of global warming, in the catastrophic effects of industrial waste and various pollutants, in the incessant production of disposable goods, in an indisputable demonstration that the capitalist mode of production does not exercise a adequateand planned domain of nature, revealing a growing contradiction between the needs for expansion of production and the conditions of the planet to provide this development. Still in this analysis, we understand that the socio-environmental issue pervades as one of the expressions of the social issue, the object of work of the social worker, which assigns him the duty of intervention also in this scope, identifying how far the profession moves towards to new directions and potentialities in the forms of intervention. In this field of complexities, the mediation and strategies of the Social Service professional have the competence to bring powerful transformations in society. However, there is a need to incorporate the socio-environmental issue in theoretical and practical professional education, especially in the discussion spaces of the category, which can collectively contribute to strengthen the political organization of the population to exercise social control, as well as to build a critical analysis about the socio-environmental crisis in the search for another form of sociability. [resumo fornecido pelo autor]
O presente estudo é um Trabalho de Conclusão do Curso de Serviço Social cujo tema central propõe abordar a questão ambiental como expressão da questão social a partir da compreensão da totalidade da realidade social contemporânea, tendo por pano de fundo, o sistema hegemônico capitalista. Com a crise ecológica atual, a sociedade mundial se deparou com o maior desafio no que tange à necessidade de mudar ações frente a esta questão. Diante de tal crise, considerada socioambiental, o Serviço Social, enquanto profissão que se inscreve no tecido das relações sociais, não deve ficar indiferente a esta temática. Assim, o problema de pesquisa consiste em compreender de que forma o profissional Assistente Social vem contribuindo frente a problemática socioambiental na sociedade contemporânea. Buscamos na trajetória desta pesquisa aprofundar a problematização das manifestações da questão socioambiental numa perspectiva sócio histórica, para refletirmos sobre as possíveis contribuições interventivas do (a) assistente social. Com base na perspectiva materialista dialética de Marx, destacando as categorias historicidade, contradição, mediação, totalidade e trabalho, procurou-se analisar refletidamente os desdobramentos e novos contornos da questão socioambiental, embalada pelo capitalismo que tem como premissa a acumulação de riquezas mediante a força de trabalho humano que abastece e gera renda aos donos dos meios de produção. Para realizar a pesquisa bibliográfica e documental, foram utilizadas fontes variadas, como legislações, artigos, livros, documentos de Conferências nacionais e internacionais, entre outros. A pesquisa parte da análise da relação existente entre homem, natureza e trabalho desde os tempos em que este buscava na natureza seu meio para a subsistência, até a produção e reprodução capitalista da atualidade e as respostas do Estado brasileiro a essas problemáticas. Buscou-se compreender também, sobre como o Assistente Social tem se inserido nas questões socioambientais e quais os desafios para o trabalho deste profissional frente a essas questões, buscando discutir sobre a importância e a necessidade de conhecer e ampliar o debate sobre a temática na área do Serviço Social. Em conclusão, percebe-se que o ecossistema tem sofrido as consequências do capitalismo e vem sendo cotidianamente destruído. Sob a égide do capital, a humanidade vem aprofundando sua trajetória de destruição da natureza, em níveis cada vez mais inquietantes. As evidências deste processo encontram-se na escassez dos recursos não renováveis, nos níveis de aquecimento planetário, nos efeitos catastróficos dos dejetos industriais e poluentes diversos, na produção incessante de mercadorias descartáveis, numa demonstração inconteste de que o modo de produção capitalista não exerce um domínio adequado e planejado da natureza, revelando uma contradição crescente entre as necessidades de expansão da produção e as condições do planeta para prover esse desenvolvimento. Ainda nessa análise, compreendemos que a questão socioambiental perpassa como uma das expressões da questão social, objeto de trabalho do (a) assistente social, o que lhe atribui o dever da intervenção também neste âmbito, identificando o quanto a profissão ascende para novos direcionamentos e potencialidades nas formas de intervenção. Neste campo de complexidades, a mediação e as estratégias do profissional do Serviço Social tem a competência de provocar potentes transformações na sociedade. Contudo, há necessidade de incorporar a questão socioambiental no ensino teórico e prático profissional, sobretudo nos espaços de discussão da categoria, podendo contribuir, coletivamente, para fortalecer a organização política da população para exercer o controle social, bem como para edificação de uma análise crítica sobre a crise socioambiental na busca por outra forma de sociabilidade. [resumo fornecido pelo autor]
Keywords: Serviço social; Politica pública; Capitalismo